Analysis Of The Implementation Of The Community Empowerment Program For Sustainable Livelihood In The Context Of Coal Mining Companies - Nurul Yakin; Budi Santosa (International Journal Labs, 2024)
Coal mining companies in fulfilling their social responsibilities through empowerment. One of the guidelines that forms the basis for the implementation of public empowerment on coal mining companies is Kepmen No. 1824 K/30/MEM Year 2018. The research is aimed at: (i) Analyzing the implementation of the community development programmes enacted by PT Arutmin Indonesia to improve the well-being of the people around the operational area; (ii) Analysing the application of community development programmes for sustainable livelihoods in the coal mining company of PT Arudmin Indonesia. The research approach is qualitative. The research site is PT Arutmin Indonesia which consists of five mine sites namely, Asamasam Mine, Kintap Mine, Satui Mine, Batulicin Mine, Senakin Mine and one North Pulau Laut Coal Terminal coal terminal. The time of the research is in one time, in 2023. Primary data collection techniques through in- depth interviews, while secondary data gathering techniques through corporate documents and reports. Data analysis techniques use the management theory of Lloyd & Aho (2020) and the sustainable living framework. The results of the research showed that PT Arutmin Indonesia demonstrated a strong commitment to effective governance in the planning, organization, leading, and controling of public empowerment programmes. Overall, the contribution of PT Arutmin Indonesia's community empowerment program to sustainable living demonstrates a balanced commitment through various contributions, with 30.51% contributing to the development of Human Capital, contributing 40.11% to Physical Capital, contribuing 14.55% to Social Capital, and contributing 6.92% to Natural Capital, as well as contributing 7.91% to Financial Capital. PT Arutmin Indonesia needs to increase attention to natural sustainability in the planning and implementation of empowerment programmes and ensure sustainable financial support, by identifying and supporting local economic projects that potentially provide long-term benefits.